Design and laying out of roads and paths in Greece for better management and development of the forest area - Liampas, Sarantis-Angelos; DROSOS, VASILEIOS (International Journal of Scientific Research and Management (IJSRM), 2018)
The forest covers everyday many human needs (e.g. recreation, walking, hiking, mountaineering, training, sports, etc.). These activities are achieved through the use of paths, which are now well developed and have taken the form of a network. During the past they constituted shaped ways by pedestrians and animals in order to join places that have for man any particular interest.Today, with technology development, in their mapping and surveying was given to them great importance, because they serve as mentioned above many activities and at the same time constitute an ecological form of road, friendlier to the environment than other classic routes.In consequence, depending on the regions we want to approach, potential users, the length, the degree of difficulty and their shape, we distinguish the paths in various categories (paths of big corridors, mountaineering paths hiking trails, peripatetic paths, educational paths and in combinations of paths). Greece except from the national trails contains also parts of two international paths (E4, E6).The design and laying out of paths is judged essential because it constitutes important tool of sustainable management. In order to laying out of the paths and the production of maps can be used several devices and instruments such as the Global Positioning System (GPS) and the electronic compass - finder (TruePulse 360° B).These devices provide us with enough information about the terrain and they contribute to the creation of topographical activities in order to develop the area as it appears in this paper. The study area is a typical semi mountainous area in the Macedonia region.The results of the measurements are presented in GIS, where the final shape of the path is appeared, and the points of measurement are given in tables. The mapping can be extended and the results of the surveying can be included in a printed or electronic map data in order to be used by stakeholders.